The Oxford handbook of sacramental theology - Boersma, Hans, 1961-; Levering, Matthew, 1971- (2015)
"As a multi-faceted introduction to sacramental theology, the purposes of this Handbook are threefold: historical, ecumenical, and missional. The forty-four chapters are organized into the following parts five parts: Sacramental Roots in Scripture, Patristic Sacramental Theology, Medieval Sacramental Theology, From the Reformation through Today, and Philosophical and Theological Issues in Sacramental Doctrine. Contributors to this Handbook explain the diverse ways that believers have construed the sacraments, both in inspired Scripture and in the history of the Church's practice. In Scripture and the early Church, Orthodox, Protestants, and Catholics all find evidence that the first Christian communities celebrated and taught about the sacraments in a manner that Orthodox, Protestants, and Catholics today affirm as the foundation of their own faith and practice. Thus, for those who want to understand what has been taught about the sacraments in Scripture and across the generations by the major thinkers of the various Christian traditions, this Handbook provides an introduction. As the divisions in Christian sacramental understanding and practice are certainly evident in this Handbook, it is not thereby without ecumenical and missional value. This book evidences that the story of the Christian sacraments is, despite divisions in interpretation and practice, one of tremendous hope"--Publisher.
Includes bibliographical references and index.
Keywords: Sacraments -- History of doctrines